2022
DOI: 10.3390/ijms23020916
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Estriol and Estrone in Keratoconic Stromal Sex Hormone Receptors

Abstract: Keratoconus (KC) is a progressive corneal thinning disease that manifests in puberty and worsens during pregnancy. KC onset and progression are attributed to diverse factors that include: environmental, genetics, and hormonal imbalances; however, the pathobiology remains elusive. This study aims to determine the role of corneal stroma sex hormone receptors in KC and their interplay with estrone (E1) and estriol (E3) using our established 3D in vitro model. Healthy cornea stromal cells (HCFs) and KC cornea stro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 54 publications
(70 reference statements)
0
20
0
Order By: Relevance
“… 15 , 45 Human corneal fibroblasts derived from patients with KC have also been found to express differential levels of androgen, estrogen, and progesterone receptors; these differences are accompanied by altered responsiveness to hormone stimulation compared with controls. 46 , 47 These findings suggest that systemic hormones, particularly estriol and estradiol, may influence corneal structure during KC.…”
Section: Discussionmentioning
confidence: 80%
“… 15 , 45 Human corneal fibroblasts derived from patients with KC have also been found to express differential levels of androgen, estrogen, and progesterone receptors; these differences are accompanied by altered responsiveness to hormone stimulation compared with controls. 46 , 47 These findings suggest that systemic hormones, particularly estriol and estradiol, may influence corneal structure during KC.…”
Section: Discussionmentioning
confidence: 80%
“…[15][16][17] It has been demonstrated that the human cornea is a sex-dependent, hormone-responsive tissue that is significantly influenced by estrogen. 18 Significant differences in steepening of the corneal curvature and thickness during normal menstrual cycle 19,20 and pregnancy 21,22 have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…To create the 3D constructs, we utilized our previously described self-assembled ECM model [ 30 , 31 ]. Briefly, HCFs and HKCs were seeded on transwell 6-well plates with polycarbonate membrane inserts with 0.4-μm pores (Transwell; Corning Costar; Charlotte, NC, USA) at a density of 1 × 10 6 cells/well and cultured in 1.5 mL of 10% FBS EMEM medium and 1% antibiotic stimulated with 0.5 mM 2-O-α-D-glucopyranosyl-L-ascorbic acid (Vitamin C, American Custom Chemicals Corporation, San Diego, CA, USA) in both top and bottom wells.…”
Section: Methodsmentioning
confidence: 99%